2022
DOI: 10.3390/ijms232213919
|View full text |Cite
|
Sign up to set email alerts
|

DRPreter: Interpretable Anticancer Drug Response Prediction Using Knowledge-Guided Graph Neural Networks and Transformer

Abstract: Some of the recent studies on drug sensitivity prediction have applied graph neural networks to leverage prior knowledge on the drug structure or gene network, and other studies have focused on the interpretability of the model to delineate the mechanism governing the drug response. However, it is crucial to make a prediction model that is both knowledge-guided and interpretable, so that the prediction accuracy is improved and practical use of the model can be enhanced. We propose an interpretable model called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Moreover, the Transformer can be trained as a generative model for de novo drug design, learning chemical space distributions and generating promising new molecules [ 64 , 66 ]. Its superior interpretability, through attention weights, allows researchers to more transparently understand the decision-making process, identifying key molecular structures or groups [ 67 ].…”
Section: Attention-based Models and Their Advantages In Drug Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the Transformer can be trained as a generative model for de novo drug design, learning chemical space distributions and generating promising new molecules [ 64 , 66 ]. Its superior interpretability, through attention weights, allows researchers to more transparently understand the decision-making process, identifying key molecular structures or groups [ 67 ].…”
Section: Attention-based Models and Their Advantages In Drug Discoverymentioning
confidence: 99%
“…Both models demonstrate superior effectiveness in predicting DRs compared with existing methods, underscoring their potential value in precision medicine. Another strategy named DRPreter stands out as an interpretable drug-response prediction model that merges biological and chemical-domain knowledge with deep learning technologies [ 67 ]. By integrating cancer-related pathways and cell line networks, it provides detailed representations and insights into drug mechanisms.…”
Section: Applications Of Attention-based Models In Drug Discoverymentioning
confidence: 99%
“…Recently, transformers have been proven to be incredibly powerful in a variety of different fields including natural language processing [ 13 ], computer vision [ 14 ], and even cancer drug response prediction. For instance, DRPreter[ 15 ] employs graph neural networks and a type-aware transformer to predict anticancer drug response, while DeepTTA [ 16 ] leverages two autoencoders to project drug and cell line features and then predict the sensitivity of the cell lines to drugs. DEERS [ 17 ] uses autoencoders and a feed-forward network to predict cell line sensitivity to drugs.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough comparison of the state-of-the-art (SOTA) models demonstrated that GraphDRP and DeepCDR outperformed traditional machine learning methods (e.g., ENet and random forest) and 3 deep learning methods (i.e., CDRscan, tCNN and MOLI) [16]. Additionally, models such as TGSA [17] and DRPreter [18] were proposed to make better use of prior domain knowledge (e.g., protein-protein interaction). They applied GNN to extract cell line features from gene networks.…”
Section: Introductionmentioning
confidence: 99%